Analysis Promotion Mix Strategies of Andjani Indonesia Semarang to Increase Sales in The Pandemic - Riandy Pratama Ambarita; Zon Vanel (Enrichment : Journal of Management, 2022)
Implementing Large-Scale Social Restrictions (PSBB) due to COVID-19 has significantly impacted sales turnover in various business sectors in Indonesia. In contrast to Andjani Indonesia Semarang, which increased sales during the pandemic by emphasizing the implementation of the promotion mix on social media. It is descriptive qualitative research. Data collection techniques carried out in this study used interviews, observation, and literature studies. This study describes the promotion mix implemented by Andjani Indonesia Semarang to increase sales during the pandemic. This study indicates that the promotion mix carried out by Andjani Indonesia Semarang, namely advertising, sales promotion, public relations, personal selling, and direct marketing, succeeded in increasing sales during the pandemic.